PENERAPAN MEDIA PEMBELAJARAN DIGITAL UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN BAHASA ARAB - Lalu Muhammad Adrian Saputra; Muhammad Afthon Ulin Nuha (Yayasan Haiah Nusratul Islam, 2025)
The development of digital technology has had a significant impact on the field of education, including in the teaching of Arabic. This article aims to examine the role of digital media in enhancing the effectiveness of Arabic language learning across various educational levels. The study was conducted using the “library research” method, which involves reviewing relevant literature sources, including books, scholarly articles, and research reports. The urgency of writing this journal is based on the pressing need to reform Arabic teaching methods to be more adaptive to technological advancements and the needs of learners in the digital era. The findings show that the use of digital media—such as interactive learning applications, educational videos, e-learning platforms, and social media—can increase learning motivation, student engagement, and accelerate the acquisition of language skills, including listening, speaking, reading, and writing. This article recommends the structured and continuous integration of digital media into the Arabic language curriculum to create learning experiences that are more dynamic, contextual, and meaningful.